The design and construction of a weld heat-affected zone simulator - Clifton, T. E.; George, M. J. (College of Aeronautics, 1968)
Investigation of the structure and properties of the heat-affected zones in welded joints is usually limited by their small size and their complexity. One method of overcoming this problem is to simulate the structure at a particular point in the heat-affected zone in a specimen of larger size by imposing on it the thermal cycle sustained at that point. The equipment described in this note uses a.c. resistance heating and water cooling to impose thermal cycles on 2.5" x O.W' x O.W' specimens, the thermal cycle being chosen by adjustment of a bank of variable resistors to construct a voltage analogue. Control of specimen temperature is achieved using a thyristor and two ignitrons to control the input at 44ov. to a welding transformer. Feedback is applied from a thermocouple welded to the specimen hot-zone. The equipment has been shown to produce the desired thermal cycles in a reproducible manner.